2010
DOI: 10.1143/jjap.49.05ff02
|View full text |Cite
|
Sign up to set email alerts
|

Novel Precursor for Development of Si–C2H4–Si Networks in SiCH for Application as a Low-k Cap Layer beyond 22 nm Nodes

Abstract: The primary x-ray diagnostic lines in He-like ions are mainly excited by electron impact from the ground level to the n = 2 levels, but at high temperatures n > 2 levels are also excited. In order to describe the atomic processes more completely, collision strengths are computed for O VII including for the first time all of the following: (i) relativistic fine structure, (ii) levels up to n = 4, and (iii) radiation damping of autoionizing resonances. The calculations are carried out using the Breit-Pauli R-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
(43 reference statements)
3
26
0
Order By: Relevance
“…403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated. 402,404 Matsuda has also shown that similar a-SiC:H films can exhibit increased fracture strength due to increased crack tip plasticity arising from the more ductile -(CH 2 ) x -bonding. 406 The combination of such ductile films with traditional low-k a-SiOC:H ILDs was also found to significantly improve the interfacial toughness of the underlying ILD/DB interface.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated. 402,404 Matsuda has also shown that similar a-SiC:H films can exhibit increased fracture strength due to increased crack tip plasticity arising from the more ductile -(CH 2 ) x -bonding. 406 The combination of such ductile films with traditional low-k a-SiOC:H ILDs was also found to significantly improve the interfacial toughness of the underlying ILD/DB interface.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
“…[402][403][404][405] Shimizu's results using precursors such as 1,1-divinyl silacyclopentane (DVScP) and 5-silaspiro- [4,4]-nonane (SSN) have shown that a-SiC:H films with a significant improvement in mass density can be achieved for a given dielectric constant relative to a-SiC:H films deposited using traditional tetramethylsilane (4MS) precursors. 403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
“…Still, some of the cyclic N\ \Si\ \N bonds were opened and broken into the small fragments such as -Si-N- [14]. Moreover, during the plasma deposition process, the vinyl side-groups in VSZ could be readily activated and reacted to form the long organic chain, such as Si-(CH 2 ) n -Si and/or Si-(CH 2 ) n -CH 3 [14,26,27]. Meanwhile, it probably also reacted with the fragment of -Si-N-to form the N-Si-C cross-linked structures.…”
Section: Resultsmentioning
confidence: 99%
“…Thin a-SiC can be used as diffusion barrier, passivation layer and a barrier layer, eg within the structure of amorphous silicon solar cells. This alloys shows to be promising also as both, etch stop [9,10] and hard mask layer [11] to assist nanoelectronic patterning, and as low dielectric constant (known as low-k) interfacial dielectric material [12], diffusion barrier [13][14][15], and pore sealants [16]. Controllability of the band gap allows a wide range of applications especially in microelectronics, including thin dielectric layers and semiconductor applications.…”
Section: Introductionmentioning
confidence: 99%